Functional Foods Phytochemicals and Health Promoting Potential - Sajid Arshad, Muhammad; Haseeb Ahmad, Muhammad (IntechOpen, 2021)
The phytochemicals present in functional foods play a vital role in boosting immunity and promoting health. This book provides a comprehensive overview of the importance of functional foods and antioxidants and their scavenging activity for preventing various health-related disorders. This book also covers the therapeutic and medicinal potential of various bioactive compounds for a healthy lifestyle, as well as examines different products containing functional ingredients that demonstrate health-promoting potential.